Исследования Генуэзской крепости Чембало в 2009 г. - Адаксина, С.Б.; Мыц, В.Л.; Ушаков, С.В. (Археологічні дослідження в Україні, 2010)
The publication is devoted to the research of Genovese fortress Chembalo: along its eastern defensive line between Barnabo Grillo towers and the Gate tower. As a result of the study the new material is obtained which allows the authors to judge about the principles of dwelling building and the development of infrastructure of the mediaeval fortress.